2018
DOI: 10.1249/mss.0000000000001418
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-induced Neural Alterations Impair Proprioception and Balance

Abstract: The current study suggests that hyperthermia impairs the proprioception and balance parameters measured. These observations might be due to heat-induced alterations in efferent and afferent signals to and from the muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…The study results contradict those achieved by Altun et al [2], who reported no statistically significant change in jump performance after heat application, and by Mtibaa et al [33], who found that hyperthermia impaired the measured proprioception and balance parameters.…”
Section: Heat Modalitycontrasting
confidence: 99%
“…The study results contradict those achieved by Altun et al [2], who reported no statistically significant change in jump performance after heat application, and by Mtibaa et al [33], who found that hyperthermia impaired the measured proprioception and balance parameters.…”
Section: Heat Modalitycontrasting
confidence: 99%
“…Participants were instructed to maintain a single leg stance with a semi-flexed knee and hands on the hips while reaching with the other leg as far as possible along the three directions. Participants had to touch the furthest point possible on the line with the most distal part of their reach foot as lightly as possible using minimal pressure to ensure that the reach leg did not provide support in the maintenance of the upright posture and that stability was achieved through balance (Mtibaa et al, 2018). Participants returned to a bilateral stance while maintaining their equilibrium.…”
Section: Balance Ability Testmentioning
confidence: 99%
“…Prolonged exercise (cycled for 2 h at a power output equal to 57–63% VO 2 max) without fluid ingestion negatively affects postural stability, whereas there is no effect after exercise with fluid replacement (intake of 1.9l of a carbohydrate-electrolyte solution) or after thermal dehydration induced by seven 15 min consecutive sauna sessions (85°C, 50% rh) with no fluid replacement ( Derave et al, 1998 ). However, more recent study by Mtibaa et al (2018) demonstrated that hyperthermia impairs the proprioception and balance parameters due to heat-induced alterations in efferent and afferent signals to and from the muscle. The exercise that induced a mild dehydration, which increases proteinemia and leads to body mass loss, was found to impair balance in the standard situation and when the vestibular cue is reliable ( Lion et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%